The influencing power of apply and explain on capital structure - Owusu, Nkwantabisa Agyeiwaa; Hadjor, Falistus Raphael; Tchuiendem, Nelly Joel (Technium Social Sciences Journal, 2021)
The paper investigated the suspension of Independent Non-Executive Directors (INEDs) stock options on corporate capital choices: Equity, retained earnings, long term borrowing and short term borrowing. The paper used a sample of 1250 non-financial Firm years from 2010 to 2019. The Ordinary Least Squares and the difference in difference method discovered that the firms’ Leverage increased positively after the reform. In particular, the suspension of stock options impacts the high levels of long term borrowing in the "Apply and Explain" periods. The study submits that the suspension of stock options maximizes the independence of the INED on the executive Board and Subcommittees (Audit and Remuneration) to reduce the use of retained earnings and promotes the use of Long term debts in financing projects.